Analysis of Human Resource Development on Employee Productivity at Puskopsyah Metro Lampung - Sugiarto; Farida, Anikmah; Rahmawati , Rita (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Empowerment is one of the suitable strategies in increasing human resources that have conformity with the performance or productivity of employees. If the human resources in a financial institution work optimally, this will have implications for an increase in the number of customers at the financial institution. This is in line with what was done by Puskopsyah Metro Lampung. This type of research is a field qualitative research and this research uses a qualitative descriptive research approach. Sources of data used are primary and secondary data sources. Data collection techniques using observation, interviews and documentation with data triangulation method. The results showed that the internal strategies used by the Central Lampung Syari'ah Cooperatives were: a) creativity, b) innovation, c) synergy between units/individuals, d) assigning responsibility and external strategies, namely: a) comparative studies, b) ) Internships, c) partnerships.